The effect of warm water foot bath therapy on the blood pressure and cortisol levels in gestational hypertension - Amin, Dewita Rahmatul; Hadisaputro, Suharyo; Isnawati, Muflihah (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2022)
Background: Pregnant women are susceptible to anxiety disorders that result in hypertension. Previous studies that have been carried out with warm water foot bath therapy, which can relax the body, previous research only measured the level of anxiety psychologically and never seen a physiological/molecular increase in blood pressure from the indicator of cortisol levels. Purpose: To analyze the effect of warm footbath therapy on the blood pressure and cortisol levels in gestational hypertension. Methods:Â This experimental study has a randomized pre-post-test control group design. They involved 40 subjects in two groups. The control group was given 10 mg of nifedipine, while the intervention group was given 10 mg of nifedipine and a warm water foot bath at 40-43oC for 15 minutes for 14 consecutive days. Pre-post cortisol levels were measured with the ELISA method cortisol test. Results:Â A warm water foot bath therapy effectively decreased systolic blood pressure in the intervention group, which was 43 mm Hg compared to the control group, 19 mm Hg (p<0.05). Diastolic blood pressure in the intervention group was 15.5 mmHg compared to the control group's 6.5 mmHg (p<0.05), and cortisol levels in the intervention group: 48.1 ng/ml compared to the control 14.5 ng/ml (p<0.05). Conclusion: Warm water foot bath therapy at 40-43oC for 15 minutes for 14 consecutive days reduces systolic blood pressure by decreasing cortisol levels in hypertensive pregnant women.